2015
DOI: 10.1016/j.atherosclerosis.2015.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the progression of carotid intima-media thickness over a 16-year follow-up period: The Malmö Diet and Cancer Study

Abstract: There were differences in the associations between risk factors and progression rate in different arterial segments. Favourable changes in SBP and lipids during the follow-up period were associated with reduced IMT progression rates in the CCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
128
3
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(140 citation statements)
references
References 44 publications
5
128
3
4
Order By: Relevance
“…We found a positive correlation between the presence of atherosclerosis and cIMT and fIMT measurements in CKD patients, suggesting that IMT values could be used to predict the presence or absence of vascular atherosclerotic disease. This is particularly observed after controlling for age, as prior studies have demonstrated that cIMT increases approximately 0.01 mm per year in both men and women [21, 22]. However, we were unable to demonstrate that IMT values could be used to predict the severity of atherosclerosis in CKD patients.…”
Section: Discussioncontrasting
confidence: 72%
“…We found a positive correlation between the presence of atherosclerosis and cIMT and fIMT measurements in CKD patients, suggesting that IMT values could be used to predict the presence or absence of vascular atherosclerotic disease. This is particularly observed after controlling for age, as prior studies have demonstrated that cIMT increases approximately 0.01 mm per year in both men and women [21, 22]. However, we were unable to demonstrate that IMT values could be used to predict the severity of atherosclerosis in CKD patients.…”
Section: Discussioncontrasting
confidence: 72%
“…From this cohort, a random sample of 6,103 individuals screened between 1991 and 1994 were selected to participate in a study aimed at studying cardiovascular risk factors, the MDC Cardiovascular Cohort (MDC-CC). All individuals from the MDC-CC were invited to participate in a reinvestigation starting in 2007 (49). Of 6,103 individuals, 3,734 (age 61-85 years) accepted and were reexamined between May 2007 and January 2012 and are included in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Following these exclusions, 4800 participants remained, constituting the sample in the present study. Individuals in the Malmö Diet and Cancer cardiovascular subcohort were invited during 2007 and 2012 (after a mean of 16 y of follow-up) to participate in a re-examination including anthropometric measurements (13). Of the 4800 participants, 3054 also had information on weight at the re-examination (Supplemental Figure 1).…”
Section: Study Populationmentioning
confidence: 99%